Measurement of Field Sound Transmission Loss of Blockwall Partition Between Two Rooms of a Tower in Jakarta - Maharani Ratna Palupi; Denny Hermawanto (Instrumentasi, 2017)
A field sound transmission loss measurement to obtain the field sound transmission class (FSTC) from partition between spaces on 27th floor Tower "A" in Jakarta was conducted in April 1st, 2017. The measurement graph showed that, although the trend indicates an increase, but the graph shape like saw tooth shape indicates sound leakages. This measurement yielded 41 dB for the FSTC rating, which is considered far from the previous expectation, about 50 dB. After further analysis, the most dominant sound leakage was contributed by flanking noise via ducting works.Keywords: field sound transmission loss measurement, field sound transmission class, FSTC, sound leakage.